Financial intermediation, resource allocation, and macroeconomic interdependence - Galip Kemal Ozhan (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
This paper studies the role of the financial sector in affecting domestic resource allocation and cross-border capital flows. I develop a quantitative, two-country, macroeconomic model in which banks face endogenous and occasionally binding leverage constraints. Banks lend funds to be invested in tradable or non-tradable sector capital and there is international financial integration in the market for bank liabilities. I focus on news about economic fundamentals as the key source of fluctuations. Specifically, in the case of positive news on the valuation of non-traded sector capital that turn out to be incorrect at a later date, the model generates an asymmetric, belief-driven boom-bust cycle that reproduces key features of the recent Eurozone crisis. Bank balance sheets amplify and propagate fluctuations through three channels when leverage constraints bind: First, amplified wealth effects induce jumps in import-demand (demand channel). Second, changes in the value of non-tradable sector assets alter bank lending to tradable sector firms (intra-national spillover channel). Third, domestic and foreign households re-adjust their savings in domestic banks, and capital flows further amplify fluctuations (international spillover channel). A common central bank's unconventional policies of private asset purchases and liquidity facilities in response to unfulfilled expectations are successful at ameliorating the economic downturn.
Keywords: E44; F32; F41; G15; G21; 330; Bank Lending; Belief-Driven Dynamics; Current Account; Macroeconomic Interdependence